Basis of forming personnel policy on the example of the Ulyanovsk region of Russia - D. A. Mukhametov; E. V. Pustynnikova (Вестник университета)
The article studies impact of personnel policy on regional development. Analysis, deduction, and description were used as general scientific methods of research. The authors studied the factors affecting availability and formation of personnel in the region, and analyzed relationship between supply and demand in labor market of the region. The innovative direction of regional economy formation and its connection with personnel policy has been emphasized. An important aspect is the development regulations, standards and qualification characteristics. The authors conclude that external and internal environments significantly affect the content of regional personnel policy. As a result of the study, principles and directions of effective regional personnel policy formation have been proposed. It is necessary to develop an effective human resources policy based on the general strategy of regional development with the inclusion of prospective goals for the use of human resources and improvement of infrastructure for developing human resources potential.